Plant mineral nutrition and disease resistance: A significant linkage for sustainable crop protection - Tripathi, Ruchi; Tewari, Rashmi; Singh, K. P.; Keswani, Chetan; Minkina, Tatiana; Srivastava, Anoop Kumar; De Corato, Ugo; Sansinenea, Estibaliz (Frontiers in Plant Science, 2022)
Complete and balanced nutrition has always been the first line of plant defense due to the direct involvement of mineral elements in plant protection. Mineral elements affect plant health both directly modulating the activity of redox enzymes or improving the plant vigor and indirectly by alteration in root exudates, changing microflora population dynamics, rhizosphere soil nutrient content, pH fluctuation, lignin deposition, and phytoalexin biosynthesis. Nitrogen (N) is one of the most important macronutrient having a significant impact on the host-pathogen axis. N negatively affects the plant’s physical defense along with the production of antimicrobial compounds, but it significantly alleviates defense related enzymes level that can eventually assist in systemic resistance.. Potassium (K) is an essential plant nutrient, when is present in adequate concentration it can certainly increase the plant’s polyphenolic concentrations, which play a critical role in the defense mechanism. Although no distinguished role of phosphorus (P) is observed in plant disease resistance, a high P content may increase the plant’s susceptibility towards the invader. Manganese is one of the most important micronutrients which has the vital effect on photosynthesis, lignin biosynthesis and other plant metabolic functions. Similarly, many other nutrients also have variable effects on enhancing or decreasing the host susceptibility towards disease onset and progression, thereby making integrative plant nutrition an indispensable component of sustainable agriculture. Thereby, the present review summarizes the recent progress regarding the use of macro- and micro-nutrients and their role in plant disease resistance.